Menstrual Migraine : How Hormones Impact Migraine - Susanti, Restu; Muhammad, Syamel (Fakultas Kedokteran Universitas Andalas, 2021)
Menstrual Migraine is divided into 2 subtypes: Menstrually Related Migraine (MRM) and Pure Menstrual Migraines (PMM). In PMM symptoms do not occur outside the menstrual cycle while MRM, symptoms can occur at other times apart from the menstrual cycle. The occurrence of menstrual migraines is related to the female hormones cycle in the form of the decrease in estrogen levels which usually occurs a week before the onset of menstruation. The mechanism is unclear, but it is thought that a decrease in estrogen levels can trigger decrease in serotonin levels, causing cranial vasodilation and sensitization of the trigeminal nerve. Â Keywords: menstrual migraine, hormones